Hybridization and its application in aquaculture - Rahman, Md. Aminur; Lee, Sang Go; Md. Yusoff, Fatimah; Rafiquzzaman, S. M. (Wiley & Sons, 2019)
Inter‐specific hybrids are usually formed by mating two different species in the same genus. They have been produced to increase growth rate, improve production performance, transfer desirable traits, reduce unwanted reproduction, combine other valuable traits such as good flesh quality, disease resistance and increase environmental tolerances, better feed conversion, and increase harvesting rate in culture systems. Hybrids play a significant role in helping to increase aquaculture production of several species of freshwater and marine fishes – for example, hybrid catfish in Thailand, hybrid striped bass in the USA, hybrid tilapia in Israel, and hybrid characids in Venezuela. As the domestication of fish species increases, the possibilities to increase production through appropriate hybridization techniques are ongoing, with a view to produce new hybrid fishes, especially in culture systems where sterile fish may be preferred because of the concern that fish may escape into the open freshwater, marine and coastal environment. Intentional or accidental hybridization can lead to unexpected results in hybrid progeny, such as reduced viability and growth performances, loss of color pattern and flesh quality, and it also raises risks for maintenance of genetic integrity. Appropriate knowledge on the genetic constitution of the brood stock, proper brood stock management, and monitoring of the viability and fertility of the progeny of brood fishes, is thus very crucial before initiating hybridization experiments. In addition, some non‐generic factors, such as weather conditions, culture systems, seasons, and stresses associated with selecting, collecting, handling, breeding and rearing of brood stock and progeny, may influence hybridization success in a wide variety of freshwater and marine fin fishes to a greater extent.